Understanding Latina/o Students' Meaning in Life, Spirituality, and Subjective Happiness. (April 2015) - Cavazos Vela, Javier; Castro, Veronica; Cavazos, Leticia; Cavazos, Michelle; Gonzalez, Stacey Lee
One-hundred nineteen Latina/o college students provided perceptions of presence of meaning in life, search for meaning in life, daily spiritual experiences, and subjective happiness. Perceptions of meaning in life and daily spiritual experiences were significant predictors of subjective happiness. A discussion regarding the importance of these findings is provided, and implications for university staff are offered.